Experimental and numerical inspection of cracks in ferrule cracking of BK1 cement crusher (Fracture and Structural Integrity, 2023)
This article defines the main actions planned in the procedure of non-destructive testing and analysis of defects in the BK1 industrial mill of the cement plant of the GICA group. One of the subjects attracting the attention of researchers and engineers was the propagation of cracks in the shell of the BK1 mill, which behaves like perforated plates. This inspection technique makes it possible to position and size defects (cracks) in the plates. The objective of this work is the detection of cracks in the shell of the BK1 cement mill. In order to avoid bursting of the crusher, the preventive technique of ultrasonic inspection using a multi-element translator is used, while minimizing downtime and increasing production. Found Results allow us to determine and analyze the different types of defects, which will be repaired. It was concluded that the stress concentration at the assembly holes, the vibration effects and gradient of the temperature due to the effect of welding were the causes great residual stresses at the level of the weld. We note the addition of a mass of weld during the repair of the cracks is one causes of the stress concentration.
Keywords: Cement crusher; ferrule; non-destructive multi-element control; crack; fatigue